Characteristics of Patients With Upper Acute Respiratory Infection in the Case of Covid-19 at Sindang Barang Community Health Center, Bogor - Avitasya Putri Rejeki; Novi Wijayanti Sukirto; Nuni Ihsana (Ahmad Dahlan Medical Journal, 2022)
Indonesia has the highest COVID-19 cases in Southeast Asia, with 1,577,526 confirmed cases. The city of Bogor alone has 14,769 confirmed cases of COVID-19. In Indonesia, the most common symptoms for COVID-19 patients are cough (63.4%) and fever (35.8%). These symptoms can also occur in upper Acute Respiratory Tract Infections (ARI), but patients with COVID-19 can have varying symptoms individually in each region.To determine the characteristics of patients with upper ARI symptoms in cases of COVID-19 at the Sindang Barang Community Health Center, Bogor City from 1 July 2020 to 31 July 2021.Quantitative research with descriptive observational research design and cross-sectional methods was employed. The total sampling technique was used with a sample of 169 people. The data source was secondary data in a form of Epidemiological Investigation (EI) data. Data analysis in this study was descriptive statistics.The results of the univariate analysis show that the highest percentage of characteristics of COVID-19 patients with upper ARI symptoms at the Sindang Barang Community Health Center, Bogor City are 36-45 years old (36.7%) with an average age of 36 years old, a minimum age of 18 years old, a maximum age of 58 years old, male (57.4 %), without comorbidities (95.9%), working as an employee (40.2%), living in Bubulak Village (35.5%), and showing cough symptoms (79.2%).